Intellectual disabilities and autism among children with congenital heart defects, Western Australia, 1983-2010 - Emine Bircan; Maria D. Politis; Yevgeniya Gokun; Chunqiao Luo; Helen Leonard; Jenny Bourke; Carol Bower; Wendy N. Nembhard (BMC, 2023)
Abstract Background Children with congenital heart defects (CHDs) are at higher risk of developing an intellectual disability. However, severity of intellectual disabilities among this group of children are largely unknown. Our objective was to determine the risk of intellectual disability (ID), ID severity, and autism among children with CHDs. Methods We conducted a retrospective cohort study of singleton live births in Western Australia (n = 20,592) between 1983 and 2010. Children with CHDs were identified from the Western Australian Register for Developmental Anomalies (n = 6563) and infants without CHDs were randomly selected from state birth records (n = 14,029). Children diagnosed with ID before 18 years were identified by linkage to statewide Intellectual Disability Exploring Answers database. Odds ratios (OR) and 95% confidence intervals (CI) were calculated from logistic regression models for all CHDs combined and by CHD severity adjusting for potential confounders. Results Of 20,592 children, 466 (7.1%) with CHDs and 187 (1.3%) without CHDs had an ID. Compared to children without CHDs, children with any CHD had 5.26 times (95% CI 4.42, 6.26) the odds of having an ID and 4.76 times (95% CI 3.98, 5.70) the odds of having mild/moderate ID. Children with any CHD had 1.76 times the odds of having autism (95% CI 1.07, 2.88), and 3.27 times the odds of having an unknown cause of ID (95% CI 2.65, 4.05) compared to children without CHD. The risk of having autism (aOR 3.23, 95% CI 1.11, 9.38), and unknown cause of ID (aOR 3.45, 95% CI 2.09, 5.70) was greatest for children with mild CHD. Conclusions Children with CHDs were more likely to have an ID or autism. Future research should elucidate underlying etiology of ID in children with CHDs.